2004
DOI: 10.1128/iai.72.10.6160-6163.2004
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Pro-Matrix Metalloproteinase 9 byFusobacterium nucleatumsubsp.nucleatumas a Mechanism To Promote the Invasion of a Reconstituted Basement Membrane

Abstract: In this study, we investigated the ability of Fusobacterium nucleatum subsp. nucleatum to increase its tissue-invasive potential by acquiring cell-associated human matrix metalloproteinase 9 (MMP-9) activity. Binding of pro-MMP-9 to fusobacteria was demonstrated by enzyme-linked immunosorbent assay. Zymography and a colorimetric assay showed that bound pro-MMP-9 can be converted into a proteolytically active form. The potential contribution of this acquired host activity in tissue invasion was demonstrated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Given the reported capacity of F. nucleatum ssp. nucleatum to bind recombinant human MMP‐9 to its cell surface (9), fusobacterial cells were incubated in a culture supernatant of lipopolysaccharide‐stimulated macrophage‐like cells and then tested for cell‐associated MMP‐9 activity by zymography. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the reported capacity of F. nucleatum ssp. nucleatum to bind recombinant human MMP‐9 to its cell surface (9), fusobacterial cells were incubated in a culture supernatant of lipopolysaccharide‐stimulated macrophage‐like cells and then tested for cell‐associated MMP‐9 activity by zymography. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported the capacity of F. nucleatum ssp. nucleatum whole cells to bind recombinant MMP‐9 (9). In this study, we showed that this bacterium was able to acquire MMP‐9 activity following incubation in a supernatant of PMA‐differentiated U937 cells stimulated by lipopolysaccharide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this may have been a result of the low concentrations of bacteria (5 × 10 6 per well) used in this assay. Notably, F. nucleatum has been reported to convert pro‐MMP‐9 into the proteolytically active form ; thus, it is possible that F. nucleatum may have similar effects on pro‐MMP‐2. Little is known about proteases expressed by F. nucleatum and their ability to degrade host tissues; therefore, future studies may be aimed at investigating these as a potential pathomechanism in periodontal tissue breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction leads to increased invasion of the pathogens in a matrigel model (i.e. a reconstituted BM) (Gendron et al, 2004).…”
Section: Periodontal Pathogens Utilize Host Mmps For Degrading Host Ementioning
confidence: 99%